INTELLECTUAL PROPERTY RIGHTS PROTECTION FOR ACTORS IN THE CREATIVE ECONOMY BASED ON INTELLECTUAL PROPERTY RIGHTS LAW NUMBER 28 OF 2014 CONCERNING COPYRIGHT - Muhammad Ansy Althafzufar; Joice Soraya (Realism: Law Review, 2024)
Intellectual property rights (IPR) are rights that are born as a result of a person's intellectual labor; hence, IPR is a legal structure of intellectual property protection as a result of the work performed by the creator or inventor. This research approach combines normative and empirical legal research with descriptive research characteristics. According to the study's findings, there is still a lack of public awareness, particularly among creative economy players, in terms of preserving their inventions and not being registered, resulting in many infringements of their works. The existence of IPR may be a source of increased income for participants in the creative economy. Intellectual Property Rights are governed by the Law of the Republic of Indonesia No. 28 of 2014 on Copyright and the Government Regulation (PP) No. 56 of 2021 on the Management of Song and/or Music Copyright Royalties. As a result, anyone who infringes Intellectual Property Rights will face legal consequences.